The effects of time of day and chronotype on anticipation timing performance in team sports athletes - Ceylan, H. I.; Günay, A. R. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study was to determine whether anticipation of timing performance (AT) of team athletes changed according to the time of day and chronotype. Forty-six male team athletes who exercise regularly at least 3 days a week, participated in the study voluntarily. The athletes were divided into two groups: morning type (MT, n = 23) and evening type or close to evening type (ET, n = 23). The AT performance at high stimulus speed of athletes (12 mph) was measured in two different time periods of the day (08.00-10.00 h, 20.00-22.00) at least 2 days interval in the laboratory environment using the counter-balanced research design. As a result of the statistical analysis, it was determined that the absolute error score (12 mph) was superior in the AT task in the morning hours (13.64±5.44 ms) compared to the evening hours (16.08±3.77 ms) (t = -2.361, p = .023, effect size: 0.34). The absolute error score in the AT task in the morning hours compared to the evening hours of the MT group was found to be significantly lower (t = -9.293, p = .000, effect size: 1.93). When the absolute error scores of the ET group measured in the AT task in the morning and evening hours were compared, a statistically significant difference was detected in favor of the evening hours. (t=3.133, p=.005, effect size: 0.65). In addition, while the absolute error scores of the MT group were found to be lower than the ET group in the morning hours (t = -5.345, p = .000, effect size: 1.57), the absolute error scores of the ET group in the evening hours was better as compared with MT group (t=4.420, p=.000, effect size: 1.30). It is extremely important that coaches or exercise specialists should take into account the concept of chronotype in order to achieve optimal cognitive performance of athletes, especially in planning specific perceptual-cognitive exercises.